PROSPECT OF INDONESIA BLACK AND WHITE PEPPERS EXPORT - Tavi Supriana; Chicka Willy Yanti (Economic Journal of Emerging Markets, 2013)
AbstractThis study analyzes the behavior of pepper exports, consisting of black pepper and white pepper, to various destination countries. The results of this study showed that black pepper exports affected by the destination country's gross domestic product (GDP), the price of white pepper, the population of the country of destination and the exchange rate against the dollar. Meanwhile, white pepper exports affected by the destination country's GDP, the population of the country of destination, the price of black pepper, white pepper prices and the exchange rate against the dollar. The results also showed that black pepper and white pepper are not mutually substituted.Keywords: pepper, exports, GDP, population, exchange rate JEL Classificaiton Numbers: F14, F19AbstrakPenelitian ini menganalisis perilaku ekspor lada, terdiri dari lada hitam dan lada putih, ke berbagai negara tujuan. Hasil penelitian ini menunjukkan bahwa ekspor lada hitam dipengaruhi oleh Pendapatan domestik bruto (PDB) negara tujuan, harga lada putih, populasi negara tujuan dan nilai tukar rupiah terhadap dolar. Sementara itu, ekspor lada putih dipengaruhi oleh PDB negara tujuan, populasi negara tujuan, harga lada hitam, harga lada putih dan nilai tukar rupiah terhadap dolar. Hasil penelitian juga menunjukkan bahwa lada hitam dan lada putih tidak saling bersubstitusi.Keywords: Lada, ekspor, PDB, populasi, kursJEL Classificaiton Numbers: F14, F19